Randomized clinical trial of trigger point infiltration with lidocaine to diagnose anterior cutaneous nerve entrapment syndrome. Issue 2 (23rd November 2012) - Boelens, O. B. A.; Scheltinga, M. R.; Houterman, S.; Roumen, R. M.
Abstract Background: Anterior cutaneous nerve entrapment syndrome (ACNES) is hardly considered in the differential diagnosis of chronic abdominal pain. Some even doubt the existence of such a syndrome and attribute reported successful treatment results to a placebo effect. The objective was to clarify the role of local anaesthetic injection in diagnosing ACNES. The hypothesis was that pain attenuation following lidocaine injection would be greater than that after saline injection. Methods: Patients aged over 18 years with suspected ACNES were randomized to receive an injection of 10 ml 1 per cent lidocaine or saline into the point of maximal abdominal wall pain just beneath the anterior fascia of the rectus abdominis muscle. Pain was recorded using a visual analogue scale (VAS; 1–100 mm) and a verbal rating scale (VRS; 0, no pain; 4, severe pain) during physical examination just before and 15–20 min after injection. A reduction of at least 50 per cent on the VAS and/or 2 points on the VRS was considered a successful response. Results: Between August 2008 and December 2010, 48 patients were randomized equally (7 men and 41 women, median age 47 years). Four patients in the saline group reported a successful response compared with 13 in the lidocaine group (P = 0·007). Conclusion: Entrapped branches of intercostal nerves may contribute to the clinical picture in some patients with chronic abdominal pain. Pain reduction following local infiltration in these patients was based on an anaesthetic mechanism and not on a placebo or a mechanical (volume) effect. Registration number: NTR2016 (Nederlands Trial Register; http://www.trialregister.nl). Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.